Group‐Velocity‐Controlled and Gate‐Tunable Directional Excitation of Polaritons in Graphene‐Boron Nitride Heterostructures. Issue 5 (26th March 2018) - Jiang, Yuyu; Lin, Xiao; Low, Tony; Zhang, Baile; Chen, Hongsheng
Abstract: A fundamental building block in nano‐photonics is the ability to directionally excite highly squeezed optical mode dynamically, particularly with an electrical bias. Such capabilities would enable the active manipulation of light propagation for information processing and transfer. However, when the optical source is built‐in, it remains challenging to steer the excitation directionality in a flexible way. Here, a mechanism is revealed for tunable directional excitation of highly squeezed polaritons in graphene‐hexagonal boron nitride ( h BN) heterostructures. The effect relies on controlling the sign of the group velocity of the coupled plasmon‐phonon polaritons, which can be flipped by simply tuning the chemical potential of graphene (through electrostatic gating) in the heterostructures. Graphene‐ h BN heterostructures thus present a promising platform toward nano‐photonic circuits and nano‐devices with electrically reconfigurable functionalities. Abstract : An approach is proposed for the tunable directional excitation of highly squeezed polaritons, by simply tuning the chemical potential of graphene in graphene‐hBN heterostructures.